Computational simulation study of the impact of isotropic GDL thermal conductivity on PEMFC characteristics - Mahmut Kaplan (Renewable Energy and Sustainable Development, 2023)
The technical capability of proton exchange membrane fuel cell (PEMFC) offers an encouraging solution to produce sustainable and clean power. The pivotal part of the PEMFCs is the gas diffusion layer (GDL) which performs critical roles in providing a pathway for reactant and product. GDL electrically connects the catalyst layer to the current collector and conducts heat generated in the electrochemical reactions. The thermal conductivity as a transport property of the GDL affects heat transfer across the cell and the overall performance. In the current work, the impact of the isotropic GDL thermal conductivity ranging 1-100 W/mK at 0.4 and 0.6 V on the cell efficiency is studied computationally using ANSYS Fluent PEMFC module. The results indicate that an increase in the GDL thermal conductivity enhances the fuel cell current density considerably up to 20 W/mK and then the impact of the GDL thermal conductivity on the performance diminishes at 0.4 and 0.6 V. The power function provided a good fit with the calculated data. The maximum current density of 1.38 A/cm2 with the more homogeneous temperature distribution and lower temperature across PEMFC is obtained at 100 W/mK. Moreover, oxygen consumption and water production augments with higher thermal conductivity, especially the regions above the cathode current collector ribs.   Received: 09 September 2023 Acepted: 29 November 2023 Published: 20 December